SUSTAINABLE SENSE OF PLACE: COWORKING SPACE DENGAN PENDEKATAN ADAPTIVE REUSE DI KAWASAN STRATEGIS KOTA BATAM - Tan, Hendy; Aguspriyanti, Carissa Dinar (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2023)
The existence of abandoned buildings in Nagoya, Batam City, can impact negatively on the sense of place and identity of the area as a strategic area for trade and services. In the context of architecture, abandoned buildings are often associated with an adaptive reuse approach. Literature studies, observations, interviews, and SWOT analysis were carried out in this descriptive qualitative research to find out how to implement the adaptive reuse approach in an abandoned building in Nagoya, Batam City. This process produced design proposals which were then analyzed to obtain deeper understanding how the application of the adaptive reuse approach can create a sustainable sense of place. The results revealed that the adaptive reuse approach to the object of research can be through the strategies of using old buildings with improved facades quality and adding a new function, which is a coworking space. Because it is relevant to the identity of trade and service areas and in accordance with the conditions of current user needs. The implementation of these design strategies could establish a sustainable sense of place in Nagoya, Batam City, through strengthening its elements including form, activity, and meaning.